1995
DOI: 10.1063/1.470573
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond study of the size-dependent charge carrier dynamics in ZnO nanocluster solutions

Abstract: The dynamics of charge carrier trapping and recombination are measured as a function of ZnO cluster diameter by ultrafast pump–probe absorption spectroscopy. A finite spherical potential well model which shows good agreement with previous experimental work is employed to predict ZnO cluster diameters from absorption onsets. The rate of electron trapping is measured for clusters of 3.2 and 6.2 nm, and is found to increase with increasing cluster size. This increase in trapping rate for increasing cluster size i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 36 publications
6
35
1
1
Order By: Relevance
“…In ZnO nanocrystals, visible broad luminescence is observed in addition to the UV luminescence and it is assigned to the transition between shallowly trapped electron and a hole deeply trapped to interior oxygen vacancy [9,38]. Cavaleri et al performed the transient infrared absorption measurements on ZnO nanocrystals dispersed in ethanol and observed efficient sub-ps electron trapping [11]. Bauer et al also observed the electron trapping to the shallow center in 20 nm size ZnO particles [12].…”
Section: Article In Pressmentioning
confidence: 94%
See 1 more Smart Citation
“…In ZnO nanocrystals, visible broad luminescence is observed in addition to the UV luminescence and it is assigned to the transition between shallowly trapped electron and a hole deeply trapped to interior oxygen vacancy [9,38]. Cavaleri et al performed the transient infrared absorption measurements on ZnO nanocrystals dispersed in ethanol and observed efficient sub-ps electron trapping [11]. Bauer et al also observed the electron trapping to the shallow center in 20 nm size ZnO particles [12].…”
Section: Article In Pressmentioning
confidence: 94%
“…To elucidate the carrier dynamics in ZnO nanocrystals Cavaleri et al measured the transient absorption by the photo-generated carriers in ZnO nanocrystals dispersed in ethanol and reported that the absorption rise time inversely depends on the particle size [11]. Bauer et al reported on the transient absorption of ZnO nanocrystal thin film and revealed the ultrafast carrier dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…An absorption peak near 480 nm super-posed on broad absorption bands in the visible range for both SPIO and MION absorption spectra is due to an indirect band gap or phonon-assisted electron transitions [13]. Other metal oxide nanoparticles, such as TiO 2 and ZnO, have been reported to have broad and extended absorption spectra [17,18].…”
Section: Absorption Measurementsmentioning
confidence: 99%
“…In particular, ZnO colloidal nanoparticles are most widely used as CBL because of their low work function, high electron mobility and optical transparency, as well as their ease of synthesis [14,18,19]. Though good performance of inverted PSCs have been reported, they can be further improved by reducing the defects in ZnO caused by adsorbed oxygen [20,21] and improving the spatial distribution of ZnO nanoparticles over a large area [22,23].…”
Section: Introductionmentioning
confidence: 98%